2017
DOI: 10.1016/j.jcv.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The fourth generation Alere TM HIV Combo rapid test improves detection of acute infection in MTN-003 (VOICE) samples

Abstract: Background Early and accurate detection of HIV is crucial when using pre-exposure prophylaxis (PrEP) for HIV prevention to avoid PrEP initiation in acutely infected individuals and to minimize the risk of drug resistance in individuals with breakthrough infection. Objective To determine if fourth-generation antigen/antibody (Ag/Ab) rapid diagnostic tests (RDT) would have detected HIV infection earlier than the third-generation RDT used in MTN-003 (VOICE). Study design 5029 VOICE participants were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
(16 reference statements)
2
20
0
Order By: Relevance
“…Taking PrEP with undetected HIV could lead to drug resistance, but a recent review of PrEP studies found that resistance selection for tenofovir disoproxil fumarate and emtricitabine with PrEP use is infrequent [28]. Evaluations of HIV rapid diagnostic tests (RDTs) among PrEP users have found variable sensitivities and specificities, with specificities >98% [29][30][31][32][33]. An evaluation of OraQuick ADVANCE â Rapid HIV-1/2, the kit we used in our study, found that it had high specificity (99.99%) and high negative predictive value (99.94%) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking PrEP with undetected HIV could lead to drug resistance, but a recent review of PrEP studies found that resistance selection for tenofovir disoproxil fumarate and emtricitabine with PrEP use is infrequent [28]. Evaluations of HIV rapid diagnostic tests (RDTs) among PrEP users have found variable sensitivities and specificities, with specificities >98% [29][30][31][32][33]. An evaluation of OraQuick ADVANCE â Rapid HIV-1/2, the kit we used in our study, found that it had high specificity (99.99%) and high negative predictive value (99.94%) [32].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of HIV rapid diagnostic tests (RDTs) among PrEP users have found variable sensitivities and specificities, with specificities >98% [29][30][31][32][33]. An evaluation of OraQuick ADVANCE â Rapid HIV-1/2, the kit we used in our study, found that it had high specificity (99.99%) and high negative predictive value (99.94%) [32]. Still, considerations about the performance of RDTs and drug resistance with undiagnosed HIV infection necessitate additional evidence on the safety and utility of HIVST in PrEP delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies of the US Food and Drug Administration (FDA)‐approved rapid Alere Determine™ HIV‐1/2 Ag/Ab Combo have shown that antigen is rarely detected in whole blood specimens, with poor sensitivity for detection of AHI. The re‐formulated Alere TM HIV Combo has shown much improved sensitivity for detection of p24 antigen , however, further evaluation of its use in clinical practice is required. Other options include diagnostic platforms for RNA testing, such as the Alere™ q HIV‐1/2 Detect which has been validated for RNA detection among infants and children, the Cepheid GeneXpert ® , the technology for which already has an existing presence in sub‐Saharan Africa where it is predominantly used for tuberculosis testing , and SAMBA which is a dipstick‐based nucleic acid assay for the detection of HIV in whole blood developed for monitoring and diagnostic use in LMIC settings.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate an increased sensitivity of the new version of the RDT for detecting early HIV-1 infection prior to seroconversion. Several studies that have recently investigated the performance of the new RDT to detect infection in p24CA-positive, immunoblot-negative serum samples showed lower reactivity rates (< 30%) [30,33], while other groups demonstrated higher reactivity rates of more than 85% in similar specimens [29,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, its reported sensitivity for the detection of HIV p24CA antigen, the critical determinant for identifying acute HIV-1 infection, varied considerably: some studies found relatively high rates of p24CA detection (> 85%) in samples from infected individuals prior to seroconversion [29,31,32]. In contrast, other studies reported considerably lower p24CA detection rates (< 30%) in similar patient cohorts [30,33]. Not surprisingly, the detection rates of the HIV antigen were particularly poor in samples from patients infected with the closely related HIV-2 [30].…”
Section: Introductionmentioning
confidence: 99%